The effect of acute and chronic exposure to hypobaric hypoxia on loaded squat jump performance - Garcia-Ramos, A.; Padial, P.; De La Fuente, B.; Arguelles-Cienfuegos, J.; Bonitch-Gongora, J.; Feriche, B. (Journal of Human Kinetics, 2017)
The present study aimed (1) to compare loaded squat jump performance after an acute and chronic exposure to a moderate natural altitude between normoxia and hypobaric hypoxia conditions, and (2) to analyze the effect of an altitude training camp on loaded jump squat development. Sixteen male swimmers (17.1 ± 0.8 years) took part in a 17-day training camp at a natural moderate altitude. They were randomly tested in counterbalanced order on days 1 and 3 in normoxia and hypoxia (pretest) and on days 15 and 17 again in normoxia and hypoxia (posttest). The peak velocity reached with loads equivalent to 25%, 50%, 75% and 100% of swimmers` pretest body weight in the loaded squat jump exercise was the dependent variable analyzed. An overall increase in peak velocity during the test performed in hypoxia of 6.5% in pretest (p < 0.001, ES = 0.98) and 4.5% in posttest (p < 0.001, ES = 0.81) was observed. An overall increment in peak velocity of 4.0% considering the data for normoxia tests (p < 0.001, ES = 0.61) and 2.1% considering the data for hypoxia tests (p = 0.008, ES = 0.36) was achieved after the altitude training camp. These results highlight the beneficial effects of hypobaric hypoxia on jump performance after short and longer term exposure to a natural moderate altitude. The increase in loaded squat jump performance following the 17-day training camp suggests that altitude training could constitute a favorable stimulus in explosive strength.